2020
DOI: 10.1152/ajpgi.00195.2019
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 inhibitor stabilizes E-cadherin and improves barrier function in experimental necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease of newborns. Although incompletely understood, NEC is associated with intestinal barrier dysfunction. E-cadherin, an adherens junction, is a protein complex integral in maintaining normal barrier homeostasis. Rho-associated protein kinase-1 (ROCK1) is a kinase that regulates the E-cadherin complex, and p120-catenin is a subunit of the E-cadherin complex that has been implicated in stabilizing the cadherin complex at the plasma membrane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Therefore, the abnormalities in E-cadherin adhesion can initiate the intercellular communication disturbance and disrupt epithelial barrier. Furthermore, the role of E-cadherin expression in the maintaining of intestinal epithelium integrity was demonstrated in the model of necrotizing enterocolitis while the disturbance in barrier function was accompanied by disruption of tight junctions (Buonpane et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abnormalities in E-cadherin adhesion can initiate the intercellular communication disturbance and disrupt epithelial barrier. Furthermore, the role of E-cadherin expression in the maintaining of intestinal epithelium integrity was demonstrated in the model of necrotizing enterocolitis while the disturbance in barrier function was accompanied by disruption of tight junctions (Buonpane et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although scarcely investigated, septic shock and experimental models of sepsis can result in a dysfunctional gastrointestinal system [159,160]. The regulation of the epithelial barrier and calcium sensitization by Rho proteins have been involved in both physiological and inflammation-associated disorders in the intestinal system [161][162][163][164][165][166][167]. The enhanced activity of RhoA was described as a determinant step for diminished epithelial resistance, leading to reduced levels of occludin and E-cadherin found in Caco-2 cells previously incubated with LPS [68].…”
Section: Rho Proteins and Their Impact On Sepsis Outside The Cardiovascular Systemmentioning
confidence: 99%
“…Intestinal epithelial tight junction (TJ) barrier dysfunction has been implicated as an important pathogenic factor of various inflammatory conditions of the gut, including inflammatory bowel disease (IBD), necrotizing enterocolitis (NEC), and celiac disease [ 1 , 2 , 3 , 4 ]. Clinical studies in IBD patients have shown that a persistent increase in intestinal permeability following clinical remission is predictive of poor clinical outcome and an early recurrence of the disease [ 5 , 6 ], while normalization of intestinal permeability correlated with a sustained long-term clinical remission.…”
Section: Introductionmentioning
confidence: 99%